Photosynthesis‐related genes induce resistance against soybean mosaic virus: Evidence for involvement of the RNA silencing pathway - Bwalya, John; Alazem, Mazen; Kim, Kook‐Hyung (Molecular plant pathology, 2022)
Increasing lines of evidence indicate that chloroplast‐related genes are involved in plant–virus interactions. However, the involvement of photosynthesis‐related genes in plant immunity is largely unexplored. Analysis of RNA‐Seq data from the soybean cultivar L29, which carries the Rsv3 resistance gene, showed that several chloroplast‐related genes were strongly induced in response to infection with an avirulent strain of soybean mosaic virus (SMV), G5H, but were weakly induced in response to a virulent strain, G7H. For further analysis, we selected the PSaC gene from the photosystem I and the ATP‐synthase α‐subunit (ATPsyn‐α) gene whose encoded protein is part of the ATP‐synthase complex. Overexpression of either gene within the G7H genome reduced virus levels in the susceptible cultivar Lee74 (rsv3‐null). This result was confirmed by transiently expressing both genes in Nicotiana benthamiana followed by G7H infection. Both proteins localized in the chloroplast envelope as well as in the nucleus and cytoplasm. Because the chloroplast is the initial biosynthesis site of defence‐related hormones, we determined whether hormone‐related genes are involved in the ATPsyn‐α‐ and PSaC‐mediated defence. Interestingly, genes involved in the biosynthesis of several hormones were up‐regulated in plants infected with SMV‐G7H expressing ATPsyn‐α. However, only jasmonic and salicylic acid biosynthesis genes were up‐regulated following infection with the SMV‐G7H expressing PSaC. Both chimeras induced the expression of several antiviral RNA silencing genes, which indicate that such resistance may be partially achieved through the RNA silencing pathway. These findings highlight the role of photosynthesis‐related genes in regulating resistance to viruses. Two photosynthesis‐related genes, PSaC and ATPsyn‐α, contribute to resistance against soybean mosaic virus via the RNA silencing pathway.